The Debtor's Construction of an Extreme Grace Period Clause in a Debt Payment Suspension Settlement Proposal as a Form of Abuse of Process - Norman David (Journal of Law, Politic and Humanities, 2026)
The Suspension of Debt Payment Obligations (PKPU) under Indonesian Law Number 37 of 2004 is conceived as a collective debt restructuring mechanism aimed at preserving business continuity while ensuring balanced protection for creditors. Normatively, PKPU grants debtors the freedom to propose composition plans, including grace period clauses, which are legitimized through creditor voting and court homologation. However, the absence of clear statutory parameters regarding the length and reasonableness of grace periods has created a normative vacuum that may be strategically exploited by debtors. In practice, this flexibility has facilitated the inclusion of extreme grace period clauses that postpone debt repayment for disproportionately long periods, particularly disadvantaging legitimate creditors who lack a dominant position within the voting structure.This research analyzes the legal construction and basis for the inclusion of extreme grace period clauses in PKPU settlement proposals and assesses whether such practices constitute an abuse of process despite formal compliance with procedural requirements. Using doctrinal legal research, the study applies statutory and conceptual approaches, supported by qualitative analysis of primary and secondary legal materials through grammatical, systematic, and teleological interpretation. The findings demonstrate that extreme and selective grace periods undermine the substantive objectives of PKPU by transforming it from a balanced restructuring mechanism into a strategic tool favoring debtors. Such practices may therefore be classified as abuse of process, highlighting the need for clearer normative standards and a more substantive judicial interpretation of good faith to strengthen creditor protection and maintain the integrity of the PKPU regime.